Development of a bulk ore sorting model for sortability assessment. (September 2019) - Li, Genzhuang; Klein, Bern; Sun, Chunbao; Kou, Jue; Yu, Lei
Highlights: A bulk ore sorting model was developed for sortability assessment. Metal distribution within ore deposits was recognized as a fractal structure. The optimum cut-off grade was determined based on model calculations. Abstract: Bulk ore sorting (BOS) has the potential to reduce processing costs and improve mine economics. A factor that impedes its acceptance is the lack of a method to assess ore amenability to sorting. In this study, a fractal model of metal distribution was used to assess an ore's bulk sortability. A BOS model was developed where metal distribution properties were characterised, optimum cut-off grade for sorter operation was determined, and economic potential of BOS was evaluated. For the developed model, the metal distribution within the ore deposits was recognised as a fractal structure. Two parameters were introduced, namely the grade factor and fractal dimension, to quantitatively characterise ore properties in terms of grade magnitude and heterogeneity. The mass balance of the sorter operation was modelled as a function of the characterised ore properties and the optimum cut-off grade was determined based on model calculations. The economic potential of BOS was evaluated in terms of the net smelter return and compared with that when no BOS was implemented. Based on the developed model, the bulk ore sortability of different ore properties was assessed with a hypothetical underground copper mine. The developed BOS model provided a powerful tool for ore sortability assessment and is expected to encourage academic research and industrial practices of BOS.